A mathematical model to study the impact of intra-tumour heterogeneity on anti-tumour CD8+ T cell immune response. (7th April 2022) - Leschiera, Emma; Lorenzi, Tommaso; Shen, Shensi; Almeida, Luis; Audebert, Chloe
Highlights: An individual-based model describing interactions between tumour and CD8 + T cells. The model takes into account tumour antigen expression and presentation. The degree of tumour heterogeneity has an impact on immune response efficacy. Wider ranges of antigens promote immune escape of tumours. Lower levels of antigen presentation diminish the immune action. Abstract: Intra-tumour heterogeneity (ITH) has a strong impact on the efficacy of the immune response against solid tumours. The number of sub-populations of cancer cells expressing different antigens and the percentage of immunogenic cells ( i.e. tumour cells that are effectively targeted by immune cells) in a tumour are both expressions of ITH. Here, we present a spatially explicit stochastic individual-based model of the interaction dynamics between tumour cells and CD8 + T cells, which makes it possible to dissect out the specific impact of these two expressions of ITH on anti-tumour immune response. The set-up of numerical simulations of the model is defined so as to mimic scenarios considered in previous experimental studies. Moreover, the ability of the model to qualitatively reproduce experimental observations of successful and unsuccessful immune surveillance is demonstrated. First, the results of numerical simulations of this model indicate that the presence of a larger number of sub-populations of tumour cells that express different antigens is associated with a reduced ability of CD8 + T cells to mount an effective anti-tumour immune response. Secondly, the presence of a larger percentage of tumour cells that are not effectively targeted by CD8 + T cells may reduce the effectiveness of anti-tumour immunity. Ultimately, the mathematical model presented in this paper may provide a framework to help biologists and clinicians to better understand the mechanisms that are responsible for the emergence of different outcomes of immunotherapy.